Disparate molecular mechanisms in cardiac ryanodine receptor channelopathies - Zhang, Yadan; Seidel, Monika; Rabesahala de Meritens, Camille; Beckmann, Astrid; Ahmed, Syeda; Hurtz, Melanie; Lai, F. Anthony; Zorio, Esther; Parthimos, Dimitris; Zissimopoulos, Spyros (Frontiers in Molecular Biosciences, 2024)
AimsMutations in the cardiac ryanodine receptor (RyR2) are associated with catecholaminergic polymorphic ventricular tachycardia (CPVT). This study investigates the underlying molecular mechanisms for CPVT mutations within the RyR2 N-terminus domain (NTD).Methods and ResultsWe consulted the high-resolution RyR2 structure in both open and closed configuration to identify mutations G357S/R407I and A77T, which lie within the NTD intra- and inter-subunit interface with the Core Solenoid (CSol), respectively. Their structural and functional roles were compared to R169L, a mutation that lies within the NTD-NTD inter-subunit interface. Using chemical cross-linking and co-immunoprecipitation assays, we show that R169L disrupts NTD tetramerization, while it does not alter the NTD-CSol interaction. Single cell Ca2+ imaging revealed that R169L increases the number of spontaneous Ca2+ transients and the proportion of oscillating cells, while reducing the Ca2+ store content. G357S and R407I do not affect NTD tetramerization, but they also do not alter the NTD-CSol interaction. Functionally, RyR2G357S-expressing cells have Ca2+ handling properties similar to RyR2WT. A77T enhances the NTD-CSol interaction, while it does not affect NTD tetramerization. Like R169L, A77T also increases the number of spontaneous Ca2+ transients and the proportion of oscillating cells, and it reduces the Ca2+ store content. However, unlike R169L that displays Ca2+ transients of normal amplitude and shorter duration, Ca2+ transients for A77T are of smaller amplitude and normal duration.ConclusionThe NTD-CSol inter-subunit interface variant, A77T, produces a hyperactive channel by altering a different structure-function parameter to other CPVT mutations within the RyR2 NTD. Reduced NTD-NTD inter-subunit interaction and reinforced NTD inter-subunit interaction with CSol are distinct molecular mechanisms for gain-of-function RyR2 arrhythmogenic mutations.